SAT0313 The link between enthesitis and arthritis in psoriatic arthritis: A switch to a vascular phenotype at insertions may play a role in arthritis development. (23rd January 2014) - Aydin, S.Z.; Ash, Z.R.; Tinazzi, I.; Castillo-Gallego, C.; Kwok, C.; Wilson, C.; Goodfield, M.; Gisondi, P.; Tan, A.L.; Marzo-Ortega, H.; Emery, P.; Wakefield, R.; et al.
Abstract : Background: Subclinical enthesopathy is recognised in both psoriasis and psoriatic arthritis (PsA). However, there is limited work directly comparing power Doppler (PD) changes at the insertions between patients with PsA and psoriasis. Objectives: This study used ultrasonography (US) with PD to test the hypothesis that subclinical enthesopathy in PsA was associated with an "inflammatory" or vascular phenotype compared to that seen in psoriasis. Methods: 100 patients with a mean (SD) age of 46 (15) (42 with psoriasis and 58 with PsA) and 23 matched healthy controls (HC) from two centres were included. A total of 1230 lower limb entheses were scanned by ultrasonographers blinded to clinical details. Both inflammatory and chronic features of enthesopathy were scored. Results: Psoriasis patients (with or without arthritis) had higher inflammation related enthesopathy scores than HC (for inflammation p<0.0001, for chronicity p=0.02, for total US scores p<0.0001). The PsA patients had higher US enthesopathy scores than psoriasis patients (inflammation p=0.04, chronicity p=0.02) and HC (inflammation p<0.0001, chronicity p=0.003). When symptomatic entheses were excluded, PsA patients still had higher PD scores than psoriasis patients (p=0.003). Doppler positivity in at least one entheseal site was observed more frequently in PsA (21/58, 36.2%) than psoriasis (4/42, 9.5%; p=0.002). The tender joint count (r2 =0.21; p=0.03) and swollen joint count (r2 =0.29; p=0.003) correlated to US scores at distant sites of subclinical enthesopathy. Conclusions: This study shows that the US appearances of subclinical enthesitis in psoriasis differ from the subclinical enthesitis in PsA, with PsA patients having more power Doppler. This is suggestive of a more inflammatory or vascular process in PsA, and offers potentially novel insights into the progression from skin to joint disease in psoriasis. Disclosure of Interest: None Declared